2019
DOI: 10.5585/remark.v18i4.16386
|View full text |Cite
|
Sign up to set email alerts
|

Gooool: motivation drivers of attitudinal and behavioral fan loyalty in Brazil

Abstract: Objective:  Football is the predominant sport in Brazil, but a better understanding of what motivates non-football and football fans is needed.Method: A conceptual model is empirically tested of the effects of six motivational drivers-Interest in Team, Socialisation, Aesthetics, Sport Knowledge, Interest in Sport, Vicarious Achievement-on both attitudinal and behavioural fan loyalty using survey data from 483 Brazilian sports fans.Originality/Relevance: a theoretical gap exists as to understanding the unique m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…However, fan loyalty requires an examination beyond behavioural traits by also involving the attitudinal component of loyalty (e.g. Cifci and Erdogan, 2016;Kang, 2017;Maderer and Holtbr€ ugge, 2018;Rosenberger et al, 2019;Wang et al, 2011;Yoon et al, 2017). Therefore, this study considers both attitudinal loyalty and behavioural loyalty.…”
Section: Theoretical Framework 21 Fan Loyaltymentioning
confidence: 99%
“…However, fan loyalty requires an examination beyond behavioural traits by also involving the attitudinal component of loyalty (e.g. Cifci and Erdogan, 2016;Kang, 2017;Maderer and Holtbr€ ugge, 2018;Rosenberger et al, 2019;Wang et al, 2011;Yoon et al, 2017). Therefore, this study considers both attitudinal loyalty and behavioural loyalty.…”
Section: Theoretical Framework 21 Fan Loyaltymentioning
confidence: 99%
“…This connection can lead to team loyalty (HEERE & JAMES, 2007;STROEBEL et al, 2021). Fans who are highly identified with the team tend to show behavioral loyalty (ROSENBERGER III et al, 2019;TAPP, 2004). Also, Yoshida et al (2015) confirm that team identification positively affected behavioral intentions, and Neale and Funk (2006) found that interest in a particular team predicts loyalty.…”
Section: 4mentioning
confidence: 99%
“…Team identification suggests an interdependence between the fan and the team he/she is connected to. For various authors, this connection can lead to team loyalty (e.g., BODET & CHANAVAT, 2010;BODET et al, 2018;HEERE & JAMES, 2007;STROEBEL et al, 2021;ROSENBERGER et al, 2019;TAPP, 2004). In this study, the relationship was significant for both groups.…”
Section: How Attitudes Towards the Team Impact Team Loyaltymentioning
confidence: 99%
“…Dentre as diversas modalidades esportivas, o futebol se destaca como a mais assistida no mundo, sendo este um setor importante na indústria do entretenimento, movimentando valores significativos de recursos financeiros ao longo dos anos (MÓSCA et al, 2009;KERN et al, 2012;NASCIMENTO et al, 2015;FERREIRA et al, 2018, BEIDERBECK et al, 2021. Um exemplo da envergadura dessa relevância está no fato de que se estima que mais da metade da população teve acesso a algum tipo de cobertura oficial da (GUTERMAN, 2013;GASPARETTO, 2013;ROSENBERGER III et al, 2019).…”
Section: Introductionunclassified